THE EFFECTIVENESS OF CONTEXTUAL TEACHING AND LEARNING IN IMPROVING STUDENTS’ READING SKILL IN PROCEDURAL TEXT (A Quasi-Experimental Study of the Second Grade Students at One Vocational School in Bandung) - Khaefiatunnisa Khaefiatunnisa (Journal of English and Education, 2015)
This study aimed to investigate the effectiveness of Contextual Teaching and Learning (CTL) approach in improving students’ reading skill in procedural text and to find out the students’ responses toward the use of CTL in learning process. The quasi experimental design was employed in this study involving two classes which were assigned as experimental and control groups. The data were collected through pretest, posttest, and interview. The data from pretest and posttest were analyzed by using SPSS to examine the effectiveness of CTL approach in improving students’ reading skill in procedural text, while the interview data were analyzed to find out the students’ responses toward the use of CTL in learning process. The findings obtained from statistical computation showed that CTL approach could improve students’ reading skill in procedural texts. In addition, the interview data showed that the use of CTL motivated students to learn and helped the students to understand the materials. Based on these findings, it is recommended that CTL approach is implemented in teaching reading procedural text.